PENGUATAN KARAKTER RELIGIUS SISWA MELALUI PROGRAM MORNING DAY DI SMK MUHAMMADIYAH 2 KALIREJO - Hasbullah, Hasbullah; Armadan, Aditia; Yanti, Dwi Sartika; Rais, Muhammad Amien; Hanafi, Ilyas Rozak (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT Religious character education through the Morning Day Program is an effort to realize the religious values ??contained in the Qur'an and Al-Hadith in a person. The purpose of this study was to determine the process of religious character education through the Morning Day Program in students at SMK Muhammadiyah 2 Kalirejo and to determine the supporting and inhibiting factors. The study used a type of field research with a qualitative approach. There were 3 subjects in this study, namely: PAI teachers, IPM and students in grades X, XI and XII. While the object in this study was the process of strengthening the religious character of the Morning Day Program. Data collection techniques used interviews, observation and documentation. The data processing techniques were data collection, data reduction, data presentation and data verification. Data analysis used descriptive analysis. The results of this study indicate that the process of religious character education for students at SMK Muhammadiyah 2 Kalirejo, namely activities such as Sapa Salam (5S), Morning Murottal, Book Study, Reading and Writing the Qur'an (BTQ), as well as Religious Fridays, Clean Fridays, and Healthy Fridays, are designed to instill religious values ??in students' daily lives. These activities are effective in forming religious habits, strengthening moral values, and increasing students' discipline in worship. The results of this study indicate that the Morning Day program not only contributes to improving students' spiritual abilities, but also builds strong and noble characters, in line with the goals of national education. The supporting factors are teacher personality, support from parents, joint commitment from the school community, and adequate facilities. The inhibiting factors are electronic media and lack of student awareness. ABSTRAK Pendidikan karakter religius melalui Program Morning Day merupakan usaha untuk mewujudkan nilai-nilai agama yang ada di dalam Al-Qur’an dan Al-Hadits ke dalam diri seseorang. Tujuan dari penelitian ini untuk mengetahui proses pendidikan karakter religius melalui Program Morning Day pada siswa di SMK Muhammadiyah 2 Kalirejo dan untuk mengetahui faktor pendukung serta penghambat. Penelitian menggunakan jenis penelitian lapangan (field research) dengan pendekatan kualitatif. Subjek dalam penelitian ini ada 3 yaitu: guru PAI, IPM dan Siswa Kelas X, XI dan XII. Sedangkan objek dalam penelitian ini proses penguatan karakter religius Program Morning Day. Teknik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Adapun teknik pengolahan data adalah pengumpulan data, reduksi data, penyajian data dan verifikasi data. Analisis data menggunakan analisis deskriptif. Hasil penelitian ini menunjukkan bahwa proses pendidikan karakter religius pada siswa di SMK Muhammadiyah 2 Kalirejo yaitu kegiatan seperti Sapa Salam (5S), Murottal Pagi, Kajian Kitab, Baca Tulis Al-Qur’an (BTQ), serta Jumat Religi, Jumat Bersih, dan Jumat Sehat, dirancang untuk menanamkan nilai-nilai keagamaan dalam kehidupan sehari-hari siswa. Kegiatan tersebut efektif dalam membentuk kebiasaan religius, memperkuat nilai moral, dan meningkatkan kedisiplinan siswa dalam beribadah. Hasil penelitian ini menunjukkan bahwa Program Morning Day tidak hanya berkontribusi pada peningkatan kemampuan spiritual siswa, tetapi juga membangun karakter yang kuat dan berakhlak mulia, sejalan dengan tujuan pendidikan nasional. Faktor pendukungnya yaitu kepribadian guru, adanya dukungan dari orangtua, komitmen bersama warga sekolah, dan fasilitas yang memadai. Faktor penghambatnya yaitu media elektronik dan kurangnya kesadaran peserta didik.